Transferabilidade de microssatélites de arroz para trigo na busca por marcadores ligados à resistência à fusariose - Carvalho, Alexandre Zanardo de (2007)
Fusarium head blight (FHB) is one of the most important diseases known to affect wheat crop. FHB, caused mainly by Fusarium graminearum, results in severe losses of productivity and grain quality besides its harmful effects to human and animal health due to the accumulation of mycotoxins in infected grains. Genetic resistance is the best way to control FHB which affects crops in several parts of the world. FHB resistance shows a quantitative heritage, hence are QTLs (quantitativetrait- loci) that have a weak effect on character. Studies with microsatellite markers have generated a great number of information related to the position of those QTLs in the genome, in addition to the development of new varieties to be used in breeding programs. The microsatellites are short sequence repeats, spread thoroughly in the organism s genome. For amplification of those sequences it is used specific primers to each loco. Due to the genetic relation between species, information generated from the study in one species can be used successfully when studying related species. Therefore, primers designed for microsatellites in one species can be used to detect markers in related species and to associating those markers with characteristics of interest. Here, the main objective of my work was to verify the transferability of microsatellites from rice to wheat in search of markers related to FHB resistance. It was tested different wheat genotypes showing different levels of resistance to Fusarium and was verified the existence of polymorphism among those genotypes. A number of 55 primer pairs of microsatellites isolated from the rice genome were tested in 13 wheat cultivars classified as susceptible, moderately susceptible, moderately resistant and resistant. In my results, the rate of microsatellite transferability was of 76.4%, where from these, 23.8% showed polymorphism and 76.2% showed monomorphism. In spite of the high rate of the microsatellite transferability observed in my results, the analysis of polymorphism did not allow the identification of markers that could be possibly associated with resistance to Fusarium head blight in wheat.